Economic valuation of integrated solid waste management in Kota Bharu, Kelantan. - Nik Nor Rahimah Binti Nik Ab rahim (2013)
Solid waste management in Kota Bharu is under responsiblity of local authority, known as Majlis Perbandaran Kota Bharu (MPKB). Solid waste management is a critical issue in Kota Bharu due to amalgamation of dwindling financial resources and population growth. These situation result in incompetency in controlling and handling excessive solid waste generation, giving rise to adverse effects on environment and public health. introducing a new policy approach, integrated solid waste management can help to enhance condition of solid waste management in terms of reducing the waste generated, efficient services and sanitary waste disposal in Kota Bharu.